A comparative study of atmospheric Maxwell current and electric field from a low latitude station, Tirunelveli - Panneerselvam, C.; Nair, K.U.; Jeeva, K.; Selvaraj, C.; Gurubaran, S.; Rajaram, R. (My University, 2003)
Simultaneous measurements of atmospheric Maxwell current and electric field, using horizontal long wire antenna and passive horizontal wire antenna system at 1 m above the Earth’s surface, were carried out at Tirunelveli (8.7°N, 77.8°E), India, during January/February 2002. The objectives of the present work have been to understand the nature of the measured atmospheric electrical parameters and explore the possibility of detecting the signature associated with the global thunderstorm activity. As the measurements indicate, the atmospheric electrical parameters at Tirunelveli are severely masked by the locally induced current components during disturbed weather conditions, for example, severe convective activity. During the selected fair weather conditions, the hourly averaged diurnal variation curves of Maxwell current and electric field are characterized by two peaks: The first peak is the local “sunrise effect” and the second peak occurs at times close to 1900 UT, the time of maximum global thunderstorm activity as noted in the famous “Carniege curve”. The correlation coefficient between the measured Maxwell current and electric field has a high value (more than 0.8) for all the fair weather days. These results support our view that this site is free from local pollution during the fair weather conditions and is suitable for long-term measurements of atmospheric electrical parameters.
Keywords: Air-Earth current; Maxwell current; Electric field; Fairweather day; Sunrise effect; Global electric circuit